Craniofacial growth and morphology among intersecting clinical categories. Issue 9 (11th February 2022) - Knigge, Ryan P.; Hardin, Anna M.; Middleton, Kevin M.; McNulty, Kieran P.; Oh, Hee Soo; Valiathan, Manish; Duren, Dana L.; Sherwood, Richard J.
Abstract: Differential patterns of craniofacial growth are important sources of variation that can result in skeletal malocclusion. Understanding the timing of growth milestones and morphological change associated with adult skeletal malocclusions is critical for developing individualized orthodontic growth modification strategies. To identify patterns in the timing and geometry of growth, we used Bayesian modeling of cephalometrics and geometric morphometric analyses with a dense, longitudinal sample consisting of 15, 407 cephalograms from 1, 913 individuals between 2 and 31 years of age. Individuals were classified into vertical facial types (hyper‐, normo‐, hypo‐divergent) and anteroposterior (A‐P) skeletal classes (Class I, Class II, Class III) based on adult mandibular plane angle and ANB angle, respectively. These classifications yielded eight facial type‐skeletal class categories with sufficient sample sizes to be included in the study. Four linear cephalometrics representing facial heights and maxillary and mandibular lengths were fit to standard double logistic models generating type‐class category‐specific estimates for age, size, and rate of growth at growth milestones. Mean landmark configurations were compared among type‐class categories at four time points between 6 and 20 years of age. Overall, morphology and growth patterns were more similar within vertical facial types than within A‐P classes and variation among A‐P classes typically nested within variation among vertical types. Further, type‐class‐associated variation in the rate and magnitude of growth in specific regions identified here may serve as targets for clinical treatment of complex vertical and A‐P skeletal malocclusion and provide a clearer picture of the development of variation in craniofacial form.